Molecular Recognition of Gangliosides and Their Potential for Cancer Immunotherapies - Krengel, Ute; Bousquet, Paula A. (Frontiers in Immunology, 2014)
Gangliosides are sialic acid-containing glycosphingolipids expressed on all vertebrate cells. They are primarily positioned in the plasma membrane, with the ceramide part anchored in the membrane and the glycan part exposed on the surface of the cell. These lipids have highly diverse structures, not the least with respect to their carbohydrate chains, with N-acetylneuraminic acid (NeuAc) and N-glycolylneuraminic acid (NeuGc) being the two most common sialic acid residues in mammalian cells. Human healthy tissue is deficient in NeuGc, but since this molecule is expressed in tumors and in human fetal tissues, it is known as an onco-fetal antigen. Gangliosides perform important functions through carbohydrate-specific interactions with proteins, for example as receptors in cell-cell recognition, which can be exploited by viruses and other pathogens, and also by regulating signaling proteins through lateral interaction in the membrane. Through both mechanisms, tumor-associated gangliosides may affect malignant progression, which makes them attractive targets for cancer immunotherapies. In this review, we describe how proteins recognize gangliosides, focusing on the molecular recognition of gangliosides associated with cancer immunotherapy, and discuss the importance of these molecules in cancer research.